2022
DOI: 10.3390/pathogens11020185
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Infectious Disease Forecasting Methods across Locations, Diseases, and Time

Abstract: Accurate infectious disease forecasting can inform efforts to prevent outbreaks and mitigate adverse impacts. This study compares the performance of statistical, machine learning (ML), and deep learning (DL) approaches in forecasting infectious disease incidences across different countries and time intervals. We forecasted three diverse diseases: campylobacteriosis, typhoid, and Q-fever, using a wide variety of features (n = 46) from public datasets, e.g., landscape, climate, and socioeconomic factors. We comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 38 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…This KFD study is the rst to demonstrate the merits of combining open-source uno cial case count data from local news and internet searches with traditional climate data to strengthen the predictive capabilities of a disease facing all of the above challenges. Forecasting models rely heavily on historic data represented as time lags to improve predictive accuracies 48,49 . Our study showed that uno cial case counts reported in news media could be used as an alternative to historic data obtained from o cial sources to produce timely and reliable nowcasting and short-term forecasting estimates.…”
Section: Discussionmentioning
confidence: 99%
“…This KFD study is the rst to demonstrate the merits of combining open-source uno cial case count data from local news and internet searches with traditional climate data to strengthen the predictive capabilities of a disease facing all of the above challenges. Forecasting models rely heavily on historic data represented as time lags to improve predictive accuracies 48,49 . Our study showed that uno cial case counts reported in news media could be used as an alternative to historic data obtained from o cial sources to produce timely and reliable nowcasting and short-term forecasting estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Within ML techniques, tree-based methods were popular among all prediction categories. Tree-based methods are often among the best performing types of prediction models [ 19 , 42 , 43 ]. For instance, XGB and, RF outperformed other traditional modeling approaches in predicting diseases such as brucellosis, avian influenza, and influenza-like illnesses across different regions of the world [a107, a167, a180].…”
Section: Discussionmentioning
confidence: 99%
“…The ML and DL methods are gaining popularity and are widely being used for a variety of disease intelligence tasks, including temporal, spatial, and risk factor predictions [ 18 ]. ML models have been shown to outperform traditional statistical techniques to give more accurate and reliable predictions [ 19 , 20 ]. The popular ML techniques most widely used in the field of ID prediction include tree-based approaches [ [20] , [21] , [22] ] and Support Vector Machines (SVM) [ [23] , [24] , [25] ] due to their ease of implementation and interpretability.…”
Section: Introductionmentioning
confidence: 99%
“…Within ML techniques, tree-based methods were popular among all prediction categories. Tree-based methods such as RF, BTR, and XGB are often among the best performing types of prediction models 9,28,29 . These models are also easy to implement, fast to compute, highly performant, and provide a form of interpretability through input feature importance, which could be the main reasons for their popularity in ID modeling 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Machine Learning (ML) and Deep Learning (DL) methods are widely used for a variety of disease intelligence tasks, including temporal, spatial, and risk factor predictions 8 . ML models have been shown to outperform traditional statistical techniques to give more accurate and reliable predictions 9,10 . The popular ML techniques most widely used in the field of ID prediction include tree-based approaches [10][11][12] and Support Vector Machines (SVM) [13][14][15] due to their ease of implementation and interpretability.…”
Section: Introductionmentioning
confidence: 99%